Amplifying the Output of a Triboelectric Nanogenerator Using an Intermediary Layer of Gallium-Based Liquid Metal Particles - Kim, Jong Hyeok; Kim, Ju Hyung; Seo, Soonmin (Nanomaterials, 2023)
The production of energy has become a major issue in today’s world. Triboelectric nanogenerators (TENGs) are promising devices that can harvest mechanical energy and convert it into electrical energy. This study explored the use of Galinstan particles in the production of TENGs, which convert mechanical energy into electrical energy. During the curing process, the evaporation of the hexane solvent resulted in a film with varying concentrations of Galinstan particles. The addition of n-hexane during ultrasonication reduced the viscosity of the polydimethylsiloxane (PDMS) solution, allowing for the liquid metal (LM) particles to be physically pulverized into smaller pieces. The particle size distribution of the film with a Galinstan concentration of 23.08 wt.% was measured to be within a few micrometers through ultrasonic crushing. As the amount of LM particles in the PDMS film increased, the capacitance of the film also increased, with the LM/PDMS film with a 23.08% weight percentage exhibiting the highest capacitance value. TENGs were created using LM/PDMS films with different weight percentages and tested for open-circuit voltage, short-circuit current, and charge amount Q. The TENG with an LM/PDMS film with a 23.08% weight percentage had the highest relative permittivity, resulting in the greatest voltage, current, and charge amount. The use of Galinstan particles in PDMS films has potential applications in wearable devices, sensors, and biomedical fields.
Keywords: dielectrics; Galinstan; Galinstan particles; liquid metal; liquid metal particles; TENG; triboelectric nanogenerators